Effect of Photocaged Isopropyl β‐d‐1‐thiogalactopyranoside Solubility on the Light Responsiveness of LacI‐controlled Expression Systems in Different Bacteria. (23rd October 2020) - Hogenkamp, Fabian; Hilgers, Fabienne; Knapp, Andreas; Klaus, Oliver; Bier, Claus; Binder, Dennis; Jaeger, Karl‐Erich; Drepper, Thomas; Pietruszka, Jörg
Abstract: Photolabile protecting groups play a significant role in controlling biological functions and cellular processes in living cells and tissues, as light offers high spatiotemporal control, is non‐invasive as well as easily tuneable. In the recent past, photo‐responsive inducer molecules such as 6‐nitropiperonyl‐caged IPTG (NP‐cIPTG) have been used as optochemical tools for Lac repressor‐controlled microbial expression systems. To further expand the applicability of the versatile optochemical on‐switch, we have investigated whether the modulation of cIPTG water solubility can improve the light responsiveness of appropriate expression systems in bacteria. To this end, we developed two new cIPTG derivatives with different hydrophobicity and demonstrated both an easy applicability for the light‐mediated control of gene expression and a simple transferability of this optochemical toolbox to the biotechnologically relevant bacteria Pseudomonas putida and Bacillus subtilis . Notably, the more water‐soluble cIPTG derivative proved to be particularly suitable for light‐mediated gene expression in these alternative expression hosts. Abstract : Extended toolbox : New photocaged IPTG derivatives with various hydrophobicities for light‐induced gene expression were synthesised and tested with three different expression host strains. The most water‐soluble compound showed superior performance, especially in Bacillus subtilis .